2004
DOI: 10.1038/sj.hdy.6800558
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker genotypes, heterozygosity and genetic interactions explain heterosis in Arabidopsis thaliana

Abstract: The underlying mechanisms for hybrid vigor or heterosis are elusive. Here we report a population of recombinant inbred lines (RILs), derived from the two ecotypes, Col and Ler, which can serve as a permanent resource for studying the molecular basis of hybrid vigor in Arabidopsis. Using a North Carolina mating design III (NCIII), we determined the additive and dominant nature of gene action in this population. We detected heterosis among crosses of RILs with one of the two parents (Col and Ler) and analyzed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 51 publications
5
39
0
1
Order By: Relevance
“…Since Arabidopsis as a weed was exposed to diverse selection pressures during its evolution, one may expect that each parent harbors complexes of genes at different loci displaying positive main effects and positive interactions for growth-related traits as a major determinant of competition and reproductive fitness. This hypothesis is in agreement with the findings of Syed and Chen (2005), who concluded that heterozygosity in individual chromosomes or segments combined with epistasis may be the reason for the observed heterosis in the related cross Col 3 Ler.…”
Section: Midparent Heterosis and Genomewide Genetic Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…Since Arabidopsis as a weed was exposed to diverse selection pressures during its evolution, one may expect that each parent harbors complexes of genes at different loci displaying positive main effects and positive interactions for growth-related traits as a major determinant of competition and reproductive fitness. This hypothesis is in agreement with the findings of Syed and Chen (2005), who concluded that heterozygosity in individual chromosomes or segments combined with epistasis may be the reason for the observed heterosis in the related cross Col 3 Ler.…”
Section: Midparent Heterosis and Genomewide Genetic Effectssupporting
confidence: 93%
“…Recent studies demonstrated a substantial amount of heterosis for biomass yield and growth-related traits with a wide variation among individual hybrids (Barth et al 2003;Meyer et al 2004). First, QTL analyses on heterosis in cross Col 3 Ler were performed with testcross progenies of RILs using a TTC design (Kearsey et al 2003) and design III (Syed and Chen 2005). A detailed analysis of heterosis for biomass-related traits in the cross C24 3 Col-0 was conducted in a previous study (Kusterer et al 2007a) and in an accompanying study (Kusterer et al 2007b, this issue) with TTC progenies of RILs.…”
mentioning
confidence: 99%
“…The additive QTL do not contribute to heterosis, while the non-additive QTL, including dominant, overdominant, and epistatic do contribute [12,15,19,22,24,25,28]. The second one is to use the measurements of heterosis as the data input to perform QTL analysis [13][14][15][24][25][26]30,43]. QTL effects for Z 1 and Z 2 in the RIL-based NCIII design provide estimates of the augmented effects a*, which measures the net contribution of the QTL to the parental difference, and d*, which measures the net contribution of the QTL to midparent heterosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis represents one of the most revolutionary advancements in crop improvement, i.e., maize [8] and rice [4]. In the genetic dissection of heterosis, NCIII design, proposed by Comstock and Robinson [9,10], is one of the most powerful and widely used mating schemes [11][12][13][14][15][16][17]. Therefore, the importance of heterosis necessitates an in-depth study of the NCIII design.…”
mentioning
confidence: 99%
“…Heterosis, or hybrid vigor, refers to the phenomenon that the progeny of diverse inbred varieties exhibit greater biomass and speed of development than the better of the two parents; however, the molecular mechanism of heterosis remains to be elucidated (Xu et al, 2005;Xie et al, 2006). The development of quantitative trait locus mapping has facilitated the investigation of heterosis (Syed and Chen, 2005). However, the phenomenon of heterosis is controlled by gene expression and regulation in the heterozygote (Xu et al, 2005;Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%